The effect of family boundary flexibility on employees’ work engagement: a study based on person-environment fit theory perspective - Yang, Dexiang; Liu, Yakun; Zhang, Huiqin; Zhang, Yuxiang (Frontiers in Psychology, 2023)
Under the impact of the era of big data and public emergency, the blurring of family-work boundaries and the increasing burden of family responsibilities will pose a great challenge to employee resilience and family work balance, which in turn will affect employees’ work engagement. Therefore, based on the person-environment fit theory, this study aims to explore the potential mechanism and boundary conditions of employee family boundary flexibility fit on work engagement. This study conducted a random sampling of enterprise employees in China. A sample of 433 participants completed a questionnaire to provide data. We conduct hierarchical regression and Bootstrap analysis to verify the hypothesis model. The study found that employees’ work engagement is significantly improved when their family boundary flexibility is matched. Family-work enrichment plays a role in mediating the impact of employees’ family boundary flexibility on work engagement. The relationship between family-work enrichment and work engagement is moderated by family support. Therefore, enterprises should respect and value each employee’s family boundary flexibility, establish family-friendly policies, and consider personal family boundary flexibility in employees’ career development planning. This will promote the enhancement of employee resilience, enable better engagement in work, improve work efficiency, and enhance the core competitiveness of enterprises.